Contribution of mulch film to microplastics in agricultural soil and surface water in China - Ren, Shu-Yan; Kong, Si-Fang; Ni, Hong-Gang (Environmental pollution (1987), 2021)
Agricultural mulch film (AMF) is deemed an important source of microplastics (MPs) in agricultural soil (AS). However, quantitating the contribution of AMFs to MPs in farmland soil and surface water remains a considerable challenge to date. In the present study, a basic framework was developed to address these concerns. First, the concentrations of MPs in soil derived from AMF abrasion (CMP) and the total MPs from all sources in AS (CTMP) were measured. Then, the ratios of CMP to CTMP, i.e., the contribution of AMFs to MPs in AS, were calculated. The contribution of AMFs to MPs in surface water via soil erosion was calculated based on CTMP values, the ratios of CMP to CTMP, soil erosion intensities (SEIs), and farmland areas. Furthermore, the potential contribution of soil erosion to MPs in the ocean was estimated. In China, the inventory of MPs in surface AS in 2018 ranged from 4.9 × 106 to 1.0 × 107 tons according to our results. AMFs contributed 10%–30% of the CTMP with certainties of 60–95%. Assuming that all MPs in AS can be exhaustively transferred to surface water via soil erosion, the national mass transfer amount of MPs (MTTMP) from AS to surface water reached 1.2 × 105−2.2 × 105 tons (∼2% of the inventory of MPs in the AS of China); the fluxes of MPs into the ocean from AS were 3.4 × 104−6.6 × 104 tons, assuming that all MPs in the AS of coastal provinces enter the ocean. It is likely that AMFs contributed 10%–30% MTTMP and fluxes of MPs to the ocean according to the ratios of CMP to CTMP. Apparently, approximately 30% of the national MTTMP (i.e., the rate of MP flux to the ocean to MTTMP) was input to the ocean.